Homophily and transitivity in dynamic network formation - Bryan S. Graham (Centre for Microdata Methods and Practice (cemmap), 2016)
In social and economic networks linked agents often share additional links in common. There are two competing explanations for this phenomenon. First, agents may have a structural taste for transitive links - the returns to linking may be higher if two agents share links in common. Second, agents may assortatively match on unobserved attributes, a process called homophily. I study parameter identifiability in a simple model of dynamic network formation with both effects. Agents form, maintain, and sever links over time in order to maximize utility. The return to linking may be higher if agents share friends in common. A pair-specific utility component allows for arbitrary homophily on time-invariant agent attributes. I derive conditions under which it is possible to detect the presence of a taste for transitivity in the presence of assortative matching on unobservables. I leave the joint distribution of the initial network and the pair-specific utility component, a very high dimensional object, unrestricted. The analysis is of the 'fixed effects' type. The identification result is constructive, suggesting an analog estimator, whose single large network properties I characterize.
Keywords: C31; C33; C35; 330; Strategic Network Formation; Homophily; Transitivity; Triads; Assortative Matching; Initial Conditions Problem; Panel Data; Fixed Effects; Soziales Netzwerk; Kollektives Handeln; Soziale Beziehungen; Nachbarschaft; Dynamische Wirtschaftstheorie; Theorie